Answer:
no no no! don't touch me there that is my no no square
Step-by-step explanation:
Answer:
have you given the solution with questions or not
Answer:
= 28/3
Step-by-step explanation:
Let's solve your equation step-by-step.
x(3)−(8)(2)−9x+72=0
Step 1: Simplify both sides of the equation.
x(3)−(8)(2)−9x+72=0
3x+−16+−9x+72=0
(3x+−9x)+(−16+72)=0(Combine Like Terms)
−6x+56=0
−6x+56=0
Step 2: Subtract 56 from both sides.
−6x+56−56=0−56
−6x=−56
Step 3: Divide both sides by -6.
−6x
−6
=
−56
−6
x=
28
3
Answer:
x=
28
3
Answer:
6
Step-by-step explanation:
base + 2(legs) = 56 (2 legs are the same because it's isosceles)
x + 2(5x - 5) = 56
x + 10x - 10 = 56
11x -10 = 56
11x = 66
x = 6
16:29:15 I think that would be it but, I'm really sorry if that's not right